2013
DOI: 10.1098/rsbl.2013.0892
|View full text |Cite
|
Sign up to set email alerts
|

Chameleons communicate with complex colour changes during contests: different body regions convey different information

Abstract: Many animals display static coloration (e.g. of feathers or fur) that can serve as a reliable sexual or social signal, but the communication function of rapidly changing colours (as in chameleons and cephalopods) is poorly understood. We used recently developed photographic and mathematical modelling tools to examine how rapid colour changes of veiled chameleons Chamaeleo calyptratus predict aggressive behaviour during male-male competitions. Males that achieved brighter stripe coloration were more likely to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
71
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 98 publications
(76 citation statements)
references
References 17 publications
5
71
0
Order By: Relevance
“…Mandrill red appears to be a dynamic trait that mirrors changes in male physiology relatively rapidly, although not as rapidly as blushing in humans, dynamic colour in chameleons (Ligon & McGraw, 2013), carotenoid-derived bill colour in birds (Faivre, Grégoire, Préault, Cezilly, & Sorci, 2003), or as fast as Darwin suggested. As red skin colour responds to changes in social status, it appears to indicate current state, rather than individual quality (Setchell & Dixson, 2001c).…”
Section: Mandrillsmentioning
confidence: 99%
“…Mandrill red appears to be a dynamic trait that mirrors changes in male physiology relatively rapidly, although not as rapidly as blushing in humans, dynamic colour in chameleons (Ligon & McGraw, 2013), carotenoid-derived bill colour in birds (Faivre, Grégoire, Préault, Cezilly, & Sorci, 2003), or as fast as Darwin suggested. As red skin colour responds to changes in social status, it appears to indicate current state, rather than individual quality (Setchell & Dixson, 2001c).…”
Section: Mandrillsmentioning
confidence: 99%
“…This study found that dwarf chameleons exhibited colour change behaviours in response to both predators taking on a brighter achromatically contrast colour in the presence of a snake compared to the bird, and also across a geographical context, background colouration and habitat morphologies. Further, they are also associated [28] with the use of colour change for social communication including male contests and courtships. They will maximize detectability to conspecifics while minimizing exposure to predators and this behaviour forms the centerpiece of our bio-inspiration model presented in this paper.…”
Section: Chromatic Behaviours In the Dwarf Chameleonmentioning
confidence: 99%
“…Such a link between coloration and camouflage would also complement our finding that stress is associated with brighter body coloration: green speckled surfaces tend to be much more exposed than uniformly dark crevices or walls, and thus green perches could be more stressful for A. aquaticus. Alternatively, rapid color change may play a role in social signaling; rapid color brightening relates to contest success in other (nonanoline) taxa (e.g., Ligon and McGraw 2013), though sex and size did not influence body color in A. aquaticus.…”
Section: Figmentioning
confidence: 99%